2021
DOI: 10.1016/j.jphotochem.2020.112857
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substitution on the solid-state fluorescence properties of styrylbenzoxazole derivatives with terminal dicyanomethylene group

Abstract: Three styrylbenzoxazole derivatives with terminal dicyanomethylene group were studied in order to understand how minor modifications brought to the benzoxazole ring influence the photoluminescence properties. The three compounds were weakly fluorescent in organic solution because of molecular motions around the styryl single bonds. The unsubstituted (1) and methoxy (2) derivatives showed clear solid-state luminescence enhancement (SLE) properties. Distinct emission characteristics were attributed to the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…It can be noticed that total PL extinction was observed for samples 1c and 1e, where deformation is the strongest. Such a deactivation pathway would be particularly original because H-bonds are generally considered to rigidify the molecular structures and activate the SLE processes of numerous fluorophores [64−67], although the opposite behaviour was recently reported by us for hydroxy-substituted PBO derivatives [68]. Clearly, dimeric structures like the ones studied in the present work would deserve more attention regarding their solid-state photophysical properties.…”
Section: Towards An Understanding Of the Contrasting Solid-state Spectroscopic Behaviourmentioning
confidence: 72%
“…It can be noticed that total PL extinction was observed for samples 1c and 1e, where deformation is the strongest. Such a deactivation pathway would be particularly original because H-bonds are generally considered to rigidify the molecular structures and activate the SLE processes of numerous fluorophores [64−67], although the opposite behaviour was recently reported by us for hydroxy-substituted PBO derivatives [68]. Clearly, dimeric structures like the ones studied in the present work would deserve more attention regarding their solid-state photophysical properties.…”
Section: Towards An Understanding Of the Contrasting Solid-state Spectroscopic Behaviourmentioning
confidence: 72%
“…This compound is indeed very weakly fluorescent in fluid organic solvents, but fluorescence intensity increases with increasing viscosity, and the PLQY reaches 0.28 in the solid state (Fig. 4a) [45]. When increasing the proportion of water into a THF solution of 2, the emission intensity at the PL maximum wavelength (584 nm) is strongly enhanced up to 45 folds (Fig.…”
Section: From Dicyanovinyl Derivatives To Styryl Dyesmentioning
confidence: 87%
“…The presence of a methoxy group on the BO ring (compound 3) does not enhance the SLE behavior, while the substitution by a hydroxy group is strongly detrimental to PL emission in the solid state. No clear MFC effect was detected for molecules 2 and 3, which arrange in densely packed crystal networks [45]. Yadav et al [44] have also reported compounds 4 and 5 with only one terminal electronwithdrawing cyano group.…”
Section: From Dicyanovinyl Derivatives To Styryl Dyesmentioning
confidence: 96%
See 2 more Smart Citations